COLLABORATIVE (PARTNERSHIP) AS A FORM OF "RESTORATIVE JUSTICE" IN CONFLICT RESOLUTION FOREST RESOURCES MANAGEMENT - Agus Surono (Jurnal Dinamika Hukum, 2016)
Conflict management of forest resources among communities around forest areas often occur in various regions, particularly in some national parks and forest management as Perhutani in Java and Inhutani outside Java. These conflicts indicate the forest resources management has not effectively made a positive impact in improving communities welfare around forest areas. Although the provisions of Article 3 in conjunction with Article 68 of Law No. 41 of 1999 on Forestry, provide the basis for communities around the forest rights of forest areas, but in reality there are still people around forest areas that do not enjoy such rights and it is this which often leads to conflicts in the management of forest resources. In the event of conflict, the solution can be done collaboratively (partnership) which is one form of restorative justice is an alternative dispute resolution (ADR).Keywords: collaborative, conflict, restorative justice, forest resources.